Effect of Clove Flower Essential Oil (Syzygium aromaticum) Addition on the Antibacterial and Antioxidant Activities of Lemongrass Essential Oil (Cymbopogon citratus) - Enny Fachriyah; Safira Kaltsum Annuru; Ismiyarto Ismiyarto; Purbowatiningrum Ria Sarjono (Jurnal Kimia Sains dan Aplikasi, 2026)
Indonesia, as a tropical country, possesses substantial potential for the development and utilization of essential oils, particularly those derived from lemongrass (Cymbopogon citratus) and clove flowers (Syzygium aromaticum). Lemongrass essential oil is rich in citral and exhibits notable antibacterial activity; however, its antioxidant activity is relatively low. In contrast, clove essential oil is predominantly composed of eugenol, a compound recognized for its strong antibacterial and antioxidant properties. This study aimed to evaluate the effect of clove essential oil addition on the antibacterial and antioxidant activities of lemongrass essential oil. The essential oils were obtained through steam distillation and characterized using gas chromatography–mass spectrometry (GC–MS). Biological activities were assessed by determining total phenolic content, antioxidant activity using the DPPH assay, and antibacterial activity against Staphylococcus aureus and Escherichia coli. The results demonstrated that the addition of clove essential oil increased the total phenolic content and enhanced both the antioxidant and antibacterial activities of lemongrass essential oil. Among the tested combinations, the 1:2 (lemongrass) ratio exhibited the strongest antioxidant activity, with an IC50 value of 14.400 mg/L, which was substantially lower than that of lemongrass essential oil alone (262.28 mg/L). In the antibacterial assay, the 2:1 ratio showed the strongest inhibitory activity against Staphylococcus aureus, whereas the 1:1 ratio was more effective against Escherichia coli. These findings indicate that the addition of clove essential oil enhances the biological activities of lemongrass essential oil, resulting in additive effects on both antioxidant and antibacterial properties. Therefore, the combination of lemongrass and clove essential oils shows promise as a natural source of antibacterial and antioxidant agents.